Enhancing infrastructure resilience in stratified soft soils: 3D modeling of progressive strength degradation in pile-supported retaining walls - Muhammad Israr Khan; Jianbo Fei; Xiangsheng Chen; Yue Chen; Muhammad Hamza (European Journal of Environmental and Civil Engineering, 2026)

Genome sequencing reveals genes under selection for olfactory transduction in highland sheep - Anees Ahmad; Muhammad Ibrahim; Muhammad Yaqoob; Muhammad Fahim; Sher Hayat Khan; Israr Ud Din; Majid Khan; Sohail Ahmad (Molecular Genetics and Genomics, 2026)
Kutta is an indigenous sheep breed found in the mountainous region of Swat, Pakistan. In this study we evaluated the performance of Kutta sheep within their natural habitat and identified genomic regions associated with environmental adaptability using whole genome sequencing. Flocks are mostly managed under a transhumant production system with year-round breeding. Kutta sheep demonstrated higher lambing efficiency under the available resources. Although the body size of rams and ewes was comparable, significant variation was observed among different age groups. Whole genome sequencing identified 15.46 million variants relative to Oar_v1.0 reference genome assembly. Exonic variants accounted for 2.3% of all protein coding gene variants and affected 6347 genes. These genes were primarily enriched in pathways related to G protein-coupled receptor signaling (700 genes) and olfactory transduction (500 genes). Selective sweep analysis detected 1930 genes within the regions of high homozygosity across the genome. Based on homozygosity patterns, biological relevance, and colocalization with known QTLs, 11 candidate genes were identified as putative selective signature. Five of these genes (OR4C6L, OR1086L, OR5AK2L, QR5T2L, OR9Q2) belonged to the olfactory receptor family. These olfactory receptor genes may contribute to high-altitude adaptation in Kutta sheep by enhancing their ability to locate food resources, recognize mates, and detect predators in challenging mountainous environments. Further screening of the OR4C6L sequence across 12 indigenous sheep breeds revealed marked differences between highland and lowland populations. Collectively, these findings provide comprehensive genomic insights into high-altitude adaptation of sheep and highlight the potential role of olfactory perception in survival and environmental fitness.

Recent advances in protein engineering and synthetic applications of amino acid oxidases - Muhammad Israr; Faiza Basheer; Yi Zhou; Muhammad Zeeshan; Fiza Ali; Shuke Wu (Bioresource Technology, 2026)

Formulation and Evaluation of Losartan Potassium Microparticles Loaded Controlled-Release Tablets: An In-Vitro Perspective - Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Saima Mahmood; Farman Shah; Naveed Ullah; Fida Muhammad; Anam Adil; Sami ul Haq; Haroon Khan (Journal of Pharmaceutical Innovation, 2026)

Non-destructive classification of type 2 diabetic teeth using LIBS-derived elemental biomarkers and machine learning - Muhammad Mustafa Dastageer; Khurram Siraj; Giorgio Saverio Senesi; Muhammad Aamir Israr; S.U. Haq (Analytica Chimica Acta, 2026)

Trends and Disparities in Mortality from Hereditary Ataxia in United States, 2000–2020: A Retrospective Analysis with Projections to 2050 - Muhammad Junaid Iqbal; Fiza Wali; Laraib Israr; Noor Ullah Khan; Hanzala Ahmed Farooqi; Fatima Naveed; Areeba Kabir; Gianluca Morganti; Anastasia Ricci; Michele Menotta (The Cerebellum, 2026)

Removal of arsenic from aqueous solution using a surface-functionalized magnetic biochar derived from Chlorella - Muhammad Irfan; Israr Masood ul Hasan; Muhammad Jafir; Chang Li; Jie Hu; Muhammad Moeen ud din; Khalid Hussain; Yixing Zhu; Liugen Zheng (Marine Pollution Bulletin, 2026)

Fabrication and In-Vitro Evaluation of Floating Tablets of Levofloxacin Hemihydrate for the Local Treatment of Helicobacter Pylori Infection - Abdullah Khan; Asif Nawaz; Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Haroon Khan; Muhammad Musa Khan; Irum Farooq; Saima Mahmood (Journal of Pharmaceutical Innovation, 2026)

Fabrication and In-Vitro and In-Vivo Assessment of Levofloxacin Beads Loaded Floating Tablets to improve Gastric Residence Time - Muhammad Israr; Kamran Ahmad Khan; Ashfaq Ahmad; Kifayat Ullah Shah; Naveed Ullah; Naheed Akhtar (Journal of Pharmaceutical Innovation, 2026)

Fabrication, Preparation and In-Vitro and In-Vivo Evaluation of Metoprolol Tartrate Controlled-Release Matrices to Establish a Correlation - Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Saima Mahmood; Sami-ul-Huq; Naveed Ullah; Anam Adil; Fida Muhammad (Journal of Pharmaceutical Innovation, 2026)

Network pharmacology and molecular docking reveal PPARγ-directed antidiabetic phytochemical compounds of Momordica charantia - Owais; Israr Hussain; Muhammad Rahiyab; Arshad Iqbal; Syed Shujait Ali; Mohamed Taha Yassin (In Silico Pharmacology, 2026)

Predictive Machine Learning for Seasonal Water Quality Insights - Zouhaib Ali; Muhammad Bilal; Sallahuddin Panhwar; Muhammad Junaid; Hareef Ahmed Keerio; Israr Hussain (Water, Air, & Soil Pollution, 2026)

Network pharmacology and molecular dynamics based elucidation of Mentha piperita phytochemicals in colorectal cancer therapy - Ruqia Sartaj; Itazaz Ul Haq; Haleema Sartaj; Muhammad Rahiyab; Abbas Khan; Israr Hussain; Li Pinyi; Muhammad Rizwan; Syed Shujait Ali; Arshad Iqbal (In Silico Pharmacology, 2026)

From micro-pixels to macro-performance: An explainable machine learning framework for xanthan gum-stabilized expansive soils via AI-assisted trainable weka segmentation - Muhammad Hamza; Wen-Bo Chen; Jing-Cheng Teng; Han-Jiang Lai; Akhtar Rehman; Muhammad Israr Khan (Journal of Cleaner Production, 2026)

In-situ sequential topotactic transformation of ZIF-8 to N-doped Zn-oxide/sulfide with defect engineering for efficient radiocesium capture - Muhammad Ikram; Toshio Yamaguchi; Iltaf Muhammad; Qirui Wang; Hongyan Liu; Shahzad Afzal; Israr Masood ul Hasan; Yongquan Zhou (Chemical Engineering Journal, 2026)

Unveiling the impact of green technological innovation and foreign remittances on greenhouse gas emissions: A path to sustainable development in India - Muhammad Israr; Huaming Song; Arsalan Tanveer; Daud Abdul; Kashif Abbass (Environment, Development and Sustainability, 2026)

Potential of mycorrhizal fungi in soil C sequestration under climate change scenario: current research and prospects - Muhammad Israr Khan; Moaiz Ur Rehman; Rubab Sarfraz; Ali Fakhar; Gil Won Kim (Mitigation and Adaptation Strategies for Global Change, 2026)

Recombination hotspots and genetic variability in foot-and-mouth disease virus genomes: a comparative genomic and phylogeographic analysis - Shahid Hussain; Zixiao Jiang; Hasnain Israr; Jadoon Khan; Muhammad Nasir Riaz; Ijaz Ali; Chengjun Wu; Pir Tariq Shah (Archives of Virology, 2026)

Metal organic frameworks derived novel metal sulfide (KCoZnS) nanosheet as an efficient collector for cesium ions - Muhammad Ikram; Hongyan Liu; Iltaf Muhammad; Qirui Wang; Shahzad Afzal; Masood Ul Hasan Israr; Asad Ali; Yongquan Zhou (Journal of Environmental Chemical Engineering, 2025)

Mapping the non-coding RNA landscape in ataxia telangiectasia: a scoping review of ATM dependent miRNA and lncRNA dysregulation - Muhammad Junaid Iqbal; Usman Ameen; Hamza Tanveer; Laraib Israr; Anastasia Ricci; Gianluca Morganti; Muhammad Jawad Khan; Michele Menotta (Molecular Biology Reports, 2025)
Ataxia-Telangiectasia (A-T) is caused by biallelic Ataxia-Telangiectasia Mutated (ATM) protein mutations and is hallmarked by neurodegeneration, immunodeficiency and cancer susceptibility. Emerging work suggests that non-coding RNAs are integral to the ATM driven DNA damage response, yet the scope of non-coding RNA perturbation in A-T has not systematically mapped. This study is done to chart and synthesize all primary evidence on ncRNA dysregulation in A-T and to identify mechanistic gaps and research priorities. The evidence base comprises a total of five studies focused exclusively on microRNAs and long non-coding RNAs. Baseline sequencing of 20 patients revealed consistent downregulation of miR-195-5p, miR-30a-5p and miR-342-3p. Low dose γ-irradiation of ATM-null lymphoblastoid cell lines produced an exaggerated bidirectional shift (8 microRNAs upregulated, 6 downregulated) versus wild-type, whereas primary T-cells showed largely ATM independent rises of miR-34a-5p and miR-182-5p. A lymphoblastoid cell lines study distinguished 22 recessive or dominant radiation-responsive microRNAs. Long non-coding RNAs profiling identified 149 transcripts that require functional ATM for induction and three uniquely upregulated in A-T cells. No circular RNA study in A-T is observed till date. The ncRNA research in A-T is nascent with five studies present a miRNA dysregulation and an ATM-dependent lncRNA surge that is lost in A-T, but leave circRNAs, neuronal tissues and functional validation unexplored. Intermediate dose stress models, total and small RNA-seq under DNA damage and oxidative stress, and CRISPR rescue/knockout screens in patient derived organoids are immediate priorities for exploring the role of ncRNAs as therapeutic targets in A-T.

Structure-guided drug repurposing and dynamics simulation reveal anti-viral candidates for Bourbon virus - Israr Hussain; Itazaz Ul Haq; Muhammad Rahiyab; Junaid Khan; Rooh Ullah; Syed Shujait Ali; Hassan Sher; Arshad Iqbal (In Silico Pharmacology, 2025)

Radiometric assessment of soil collected from apple orchards in Pishin, Balochistan and associated health hazards - Israr Ullah; Nisar Ahmad; Muhammad Bakhsh (Isotopes in Environmental and Health Studies, 2025)

Utilizing genetic resources to develop yellow rust-resistant and high-yielding wheat genotypes across diverse environments - Hassan Mujtaba; Fahim Ullah Khan; Muhammad Sufyan; Israr Ud Din; Manzoor Ahmad; Asad Shah; Umair Bin Qasim (Genetic Resources and Crop Evolution, 2025)

Genetic diversity in wheat landraces for agronomic traits and yellow rust resistance - Shamim Khan; Niaz Ali; Fahim Ullah Khan; Israr Ud Din; Muhammad Amjad; Israr Ahmad (Genetic Resources and Crop Evolution, 2025)

Quantifying LID impact: A modified metric for enhanced flood mitigation and urban resilience - Shakeel Ahmad; Haifeng Jia; Anam Ashraf; Dingkun Yin; Zhengxia Chen; Rasheed Ahmed; Muhammad Israr (Resources, Conservation and Recycling, 2025)

Enhancement of photocatalytic activity of carbon nitride/black phosphorus/tungsten disulfide (CN/BP/WS2) heterojunctions via nickel doping in the hydrogen evolution reaction - Eminegül Genc Acar; Begümhan Karapınar Koç; Muhammad Israr; Emre Aslan; Orhan Altan; İmren Hatay Patır; Önder Metin (Journal of Environmental Chemical Engineering, 2025)

Molecular phylogeny and cryptic species identification of the genus Triplophysa in the freshwater of Malakand division, Pakistan - Omer dad; Muhammad Fiaz Khan; Akhtar Rasool; Mohammad Attaullah; Muhammad Israr; Naveed Akhtar (Zoologischer Anzeiger, 2025)

Role of the plant nurseries in spread of invasive alien plant species in Pakistan’s subtropical region; A threat for urban greening - Maria Shah; Shujaul Mulk Khan; Fazal Manan; Jawad Hussain; Zohaib U. Din; Imranullah Shah; Muhammad Arshad; Israr Ahmad (Urban Forestry & Urban Greening, 2025)

Building resilient urban drainage systems by integrated flood risk index for evidence-based planning - Shakeel Ahmad; Xuanrong Peng; Anam Ashraf; Dingkun Yin; Zhengxia Chen; Rasheed Ahmed; Muhammad Israr; Haifeng Jia (Journal of Environmental Management, 2025)

Advances in biosynthesis of 7-Dehydrocholesterol through de novo cell factory strategies - Yuchen Han; Yawen Huang; Muhammad Israr; Huanhuan Li; Wuyuan Zhang (Bioresource Technology, 2025)

Application of fertilizers improves cadmium phytoextraction efficiency of Nasturtium officinale R.Br. grown in cadmium-contaminated water - Amjad Ali; Niaz Ali; Yansheng Gu; Nisar Ahmad; Nasar Ali; Israr Ahmad; Ajab Khan; Muhammad Anas; Hamad Ur Rehman; Asmat Ali; Muhammad Inayat Ullah khan (Environmental Monitoring and Assessment, 2025)

Integrated debris flow hazard and risk assessment using UAV data and RAMMS, a case study in northern Pakistan - Naseem Ahmad; Muhammad Shafique; Mian Luqman Hussain; Israr Ullah (Natural Hazards, 2025)

Debris flow simulations for hazard, vulnerability and risk assessment in the Karakorum mountain ranges, northern Pakistan - Israr Ullah; Muhammad Shafique; Ghazanfar Ali Khattak; Attaullah Shah (Remote Sensing Applications: Society and Environment, 2024)

Prediction of surface urban heat island based on predicted consequences of urban sprawl using deep learning: A way forward for a sustainable environment - Shun Fu; Lufeng Wang; Umer Khalil; Ali Hassan Cheema; Israr Ullah; Bilal Aslam; Aqil Tariq; Muhammad Aslam; Saad S. Alarifi (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Enhanced capacity of thiol-functionalized sugarcane bagasse and rice husk biochars for arsenite sorption in aqueous solutions - Israr Masood ul Hasan; Nabeel Khan Niazi; Irshad Bibi; Fazila Younas; Fahad Al-Misned; Muhammad Bilal Shakoor; Fawad Ali; Shazia Ilyas; Muhammad Mahroz Hussain; Jinli Qiao; Andreas Lüttge (Environmental Science and Pollution Research, 2024)
The utilization of biowastes for producing biochar to remove potentially toxic elements from water represents an important pathway for aquatic ecosystem decontamination. Here we explored the significance of thiol-functionalization on sugarcane bagasse biochar (Th/SCB–BC) and rice husk biochar (Th/RH–BC) to enhance arsenite (As(III)) removal capacity from water and compared their efficiency with both pristine biochars (SCB–BC and RH–BC). The maximum As(III) sorption was found on Th/SCB–BC and Th/RH–BC (2.88 and 2.51 mg g −1 , respectively) compared to the SCB–BC and RH–BC (1.51 and 1.40 mg g −1 ). Relatively, a greater percentage of As(III) removal was obtained with Th/SCB–BC and Th/RH–BC (92% and 83%, respectively) at a pH 7 compared to pristine SCB–BC and RH–BC (65% and 55%) at 6 mg L −1 initial As(III) concentration, 2 h contact time and 1 g L −1 sorbent dose. Langmuir ( R 2 = 0.99) isotherm and pseudo-second-order kinetic ( R 2 = 0.99) models provided the best fits to As(III) sorption data. Desorption experiments indicated that the regeneration ability of biochars decreased and it was in the order of Th/SCB–BC (88%) > Th/RH–BC (82%) > SCB–BC (77%) > RH–BC (69%) up to three sorption–desorption cycles. Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy results demonstrated that the thiol (-S–H) functional groups were successfully grafted on the surface of two biochars and as such contributed to enhance As(III) removal from water. Spectroscopic data indicated that the surface functional moieties, such as -S–H, − OH, − COOH, and C = O were involved to increase As(III) sorption on thiol-functionalized biochars. This study highlights that thiol-grafting on both biochars, notably on SCB–BC, enhanced their ability to remove As(III) from water, which can be used as an effective technique for the treatment of As from drinking water. Graphical Abstract

Partitioning carbon dioxide emissions from soil organic matter and urea in warm and cold cropping seasons - Muhammad Israr Khan; Rubab Sarfraz; Taeyoung Kim; Hye-Jin Park; Pil Joo Kim; Gil Won Kim (Atmospheric Pollution Research, 2024)

Minimizing the total petroleum hydrocarbon contaminants in biochar derived from agricultural byproducts - Muhammad Israr Khan; Rubab Sarfraz; Pil Joo Kim; Gil Won Kim (Journal of Cleaner Production, 2024)

Rainwater harvesting for agriculture development using multi-influence factor and fuzzy overlay techniques - Xiangtian Zheng; Abid Sarwar; Fakhrul Islam; Abdul Majid; Aqil Tariq; Muhammad Ali; Shazia Gulzar; Muhammad Ismail Khan; Muhammad Akmal Sardar Ali; Muhammad Israr; Ahsan Jamil; Muhammad Aslam; et al. (Environmental Research, 2023)

Elucidating growth and biochemical characteristics of rice seedlings under stress from chromium VI salt and nanoparticles - Maryam Noor; Arif Ullah; Muhammad Israr Khan; Irum Raza; Muhammad Iqbal; Abdul Aziz; Gil Won Kim; Nadia Taimur; Azizullah Azizullah; Imran Ali; Pil Joo Kim (Environmental Science and Pollution Research, 2023)

The effect of Ni and Co co-catalysts on the catalytic activity of mesoporous graphitic carbon nitride/black phosphorus/molybdenum disulfide heterojunctions in solar-driven hydrogen evolution - Gizem Yanalak; Begümhan Karapınar Koç; Seda Yılmaz; Muhammad Israr; Mustafa Ersoz; Onder Metin; Imren Hatay Patir (Journal of Environmental Chemical Engineering, 2023)

Strength Mechanism of a Swelling Soil Improved with Jute Fibers: A Laboratory Treatment - Muhammad Wasim Tariq; Jahanzaib Israr; Khalid Farooq; Hassan Mujtaba (Geotechnical and Geological Engineering, 2023)

NIR-degradable and biocompatible hydrogels derived from hyaluronic acid and coumarin for drug delivery and bio-imaging - Muhammad Gulfam; Sung-Han Jo; Trung Thang Vu; Israr Ali; Ali Rizwan; Soo-Bin Joo; Sang-Hyug Park; Kwon Taek Lim (Carbohydrate Polymers, 2023)

Landslide hazard, susceptibility and risk assessment (HSRA) based on remote sensing and GIS data models: a case study of Muzaffarabad Pakistan - Muhammad Nasar Ahmad; Zhenfeng Shao; Rana Waqar Aslam; Israr Ahmad; Ming Liao; Xianyi Li; Yang Song (Stochastic Environmental Research and Risk Assessment, 2022)

Evaluation of agro-morphological traits, seed characterization and genetic diversity of local rice (Oryza sativa L.) varieties of Pakistan - Urooj Fazal; Israr Ud Din; Amir Muhammad Khan; Fahim Ullah Khan; Mudassar Nawaz Khan; Navid Iqbal; Muhammad Ibrahim; Sajid Ali Khan Bangash (Genetic Resources and Crop Evolution, 2022)

Assessment of municipal solid waste landfilling practices on the groundwater quality and associated health risks: a case study of Mardan-Pakistan - Muhammad Israr; Shahla Nazneen; Ali Raza; Neelum Ali; Said Akbar Khan; Hizbullah Khan; Sardar Khan; Jawad Ali (Arabian Journal of Geosciences, 2022)

The potential of microbes and sulfate in reducing arsenic phytoaccumulation by maize (Zea mays L.) plants - Natasha; Irshad Bibi; Khalid Hussain; Rabia Amen; Israr Masood Ul Hasan; Muhammad Shahid; Safdar Bashir; Nabeel Khan Niazi; Tariq Mehmood; Hafiz Naeem Asghar; Muhammad Farrakh Nawaz; Muhammad Mahroz Hussain; et al. (Environmental Geochemistry and Health, 2021)

Correction to: Lineament mapping for a part of the central Sulaiman fold–Thrust Belt (SFTB), Pakistan - Ali Abbas Wajid; Muhammad Anees; Shams ul Alam; Jodat Kamran Gorchani; Khurram Shahzad; Asif Israr; Muhammad Shafique (Arabian Journal of Geosciences, 2021)

Lineament mapping for a part of the Central Sulaiman Fold–Thrust Belt (SFTB), Pakistan - Ali Abbas Wajid; Muhammad Anees; Shams ul Alam; Jodat Kamran Gorchani; Khurram Shahzad; Asif Israr; Muhammad Shafique (Arabian Journal of Geosciences, 2021)
This study aims to analyze the lineaments using the field data and a remote sensing approach, to describe their relationship with the folds, faults, and regional tectonic stress of the central Sulaiman Fold-Thrust Belt. Joint data, from nine anticlines, has been collected using the scanline method and classified into three sets (JS1, JS2, and JS3) based on their geometrical relationships. Lineaments extracted from the 30 m digital elevation model have been classified subsequently into three lineament sets (LS1, LS2, and LS3) based on the azimuths from the corresponding joint sets. A very high correlation coefficient (rs = 0.97), between the azimuths of the field joints and the remotely sensed lineaments, has been observed which validates that the lineaments are the regional representation of the local field joints. The geometrical relationship of the lineament sets with the fold hinges indicates that the older LS1 and LS2 are strongly related to the regional folding episode, while the younger LS3 is a result of local shears. The chronological interpretation of the deformational events responsible for the lineament sets is constrained by the presence of the Kingri Fault, which induces a strike-slip component within the study area. Furthermore, the controls on the joint and lineament sets, established using multivariate statistics to decipher the effects of lithological and structural contrasts on the lineament density, reveal that an increase in the lineament density can be attributed to the competence and thickness of the rock units as well as the variable local stresses across the different folds. Based on the orientations of these lineament sets, the cumulative direction of the compressive event in the NW-SE direction (310–320) coincides with the regional stress direction of the SFTB.

Heavy Metals Assessment in Water, Sediments, Algae and Two Fish Species from River Swat, Pakistan - Israr Alam; Muhammad Nasir Khan Khattak; Shahi Mulk; Farman Ullah Dawar; Lubna Shahi; Ihsanullah Ihsanullah (Bulletin of Environmental Contamination and Toxicology, 2020)

Dioxin leaching risk assessment through selected soils by estimating distribution coefficient and breakthrough curves - Nida Gul; Bushra Khan; Hizbullah Khan; Muhammad Israr (Environmental Monitoring and Assessment, 2018)